The Dynamic Macroeconomic Effects of Tax Policy in an Overlapping Generations Model - Heijdra, Ben.; Ligthart, Jenny (Washington, D.C. : International Monetary Fund, 1998)
The paper studies the dynamic allocation effects of tax policy in the context of an overlapping generations model of the Blanchard-Yaari type. The model is extended to allow for endogenous labor supply and three tax instruments: a capital income tax, labor income tax, and consumption tax. Analytical expressions and simple diagrams are used to discuss the impact, transition, and long-run effects of tax policy changes. It is shown that a part of the long-run incidence of capital and consumption taxes falls on capital when households' horizons are finite, whereas labor would fully bear the burden of these taxes in an infinite horizon model.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet